The longitudinal impact of self-efficacy and career goals on objective and subjective career success. - Abele, Andrea E.; Spurk, Daniel (Journal of Vocational Behavior, 2009)
The present research reports on the impact of occupational self-efficacy and of career-advancement goals on objective (salary, status) and subjective (career satisfaction) career attainments. Seven hundred and thirty four highly educated and full-time employed professionals answered questionnaires immediately after graduation, three years later, and seven years later. Controlling for discipline, GPA at master's level, and gender, we found that occupational self-efficacy measured at career entry had a positive impact on salary and status three years later and a positive impact on salary change and career satisfaction seven years later. Career-advancement goals at career entry had a positive impact on salary and status after three years and a positive impact on status change after seven years, but a negative impact on career satisfaction after seven years. Women earned less than men, but did not differ from men in hierarchical status and in career satisfaction. Theoretical implications for socio-cognitive theorizing and for career-success research as well as applied implications for vocational behavior are discussed. (PsycINFO Database Record (c) 2014 APA, all rights reserved)
Keywords: self-efficacy; career goals; career success; employed professionals